Achilles Tendon Pain in Male Professional Football Players - A Prospective Five-Season Study of 88 Injuries from the UEFA Elite Club Injury Study - Waldén M; Gajhede Knudsen M; Ekstrand J; Hägglund M; D’Hooghe P; Alfredson H; Bengtsson H (Open Access Journal of Sports Medicine)
Markus Waldén,1,2 Mariann Gajhede Knudsen,1 Jan Ekstrand,1,2 Martin Hägglund,1,3 Pieter D’Hooghe,4 Håkan Alfredson,5,6 Håkan Bengtsson1,2 1Football Research Group, Linköping University, Linköping, Sweden; 2Unit of Public Health, Department of Medical, Health and Caring Sciences, Linköping University, Linköping, Sweden; 3Unit of Physiotherapy, Department of Medical, Health and Caring Sciences, Linköping University, Linköping, Sweden; 4Orthopaedic Surgery, Aspetar Qatar Orthopaedic and Sports Medicine Hospital, Doha, Qatar; 5Department of Community Medicine and Rehabilitation, Sports Medicine, Umeå University, Umeå, Sweden; 6Alfredson Tendon Clinic, Malmö, SwedenCorrespondence: Markus Waldén, Unit of Public Health, Department of Medical, Health and Caring Sciences, Linköping University, Linköping, 581 83, Sweden, Email markus.walden@telia.comPurpose: The objective was to describe the location, examination procedures, diagnoses, and treatment for gradual-onset Achilles tendon pain in male professional football (soccer) players.Patients and Methods: Forty-seven teams were followed prospectively for at least one season from 2013/14 to 2017/18. Time-loss injuries were recorded by the teams’ medical staffs. For all non-contact Achilles tendon injuries, a specific Achilles tendon form was sent to teams.Results: There were 88 time-loss injuries recorded with gradual-onset Achilles tendon pain amongst 72 players; 22 (25%) of them were severe lasting more than four weeks including one career-ending injury. The specific form was returned for 78 injuries (89%) with 55 cases (71%) having midportion and 23 cases (29%) insertional pain. There were 51 cases (65%) being examined with ultrasound and 29 cases (37%) with magnetic resonance imaging, both modalities being used in 18 cases (23%). Tendinopathy was the most frequently reported main diagnosis both for midportion and insertional pain with 60 cases (77%), but multiple diagnoses were recorded in 21 cases (27%). Surgery was performed in six cases (8%), and the majority of players were exposed to several non-surgical treatments in various combinations, with eccentric training and cryotherapy being most frequent with 52 cases (72%) each.Conclusion: Tendinopathy was the most frequent diagnosis both for midportion and insertional pain. Imaging was carried out for most injuries. A majority of injuries were managed non-surgically, with eccentric training and cryotherapy being the most frequently applied treatments.Keywords: athletic injuries, elite, imaging, rehabilitation, tendinopathy